HERMENEUTIKA FENOMENOLOGIS DALAM STUDI LIVING HADITS - Masykur Wahid (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2015)
This paper discusses about Ricoeur’s phenomenological hermeneutics. It is a method based on the text interpretation. Author interested in the phenomenon of religiosity in the study of living hadith. It raises the question, what is Ricoeur's phenomenological hermeneutics and how it can be applied? Ricoeur's phenomenological hermeneutics is a synthesis of hermeneutics and phenomenology. In its application, utilizing the text paradigm, the interpretation should be developed through three stages: semantics, reflective and existential. It concludes that the phenomenological hermeneutics can analyze the phenomenon of religiosity that produces eschatology.